2019
DOI: 10.1364/ome.9.001441
|View full text |Cite
|
Sign up to set email alerts
|

Reduced ionic effect and accelerated electro-optic response in a 2D hexagonal boron nitride planar-alignment agent based liquid crystal device

Abstract: The presence of excess free-ion impurities in liquid crystals (LCs) gives rise to a number of problems in the electro-optical liquid crystal displays (LCDs), e.g., slow electro-optical responses and image sticking effects. Here we experimentally present that the two-dimensional (2D) hexagonal boron nitride (h-BN) nanosheet can serve as a planar-alignment agent and as an ion-capturing agent at the same time in an electro-optic LC device. The 2D h-BN nanosheet is employed as a planar-alignment agent on one side … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…For example, the epitaxial interactions between the nematic LC and the hexagonal lattice of graphene, molybdenum diselenide, and tungsten diselenide deposited [1][2][3][4][5][6][7][8][9][10] demonstrate that the LC can achieve a planar-aligned state on these 2D hexagonal nanostructures. Our group has recently shown that the 2D hexagonal boron nitride (h-BN) film can be successfully employed as a planar-alignment agent as well as an ion-capturing agent in electro-optic LC devices [11][12][13]. Here we report the effects of ultrafine 2D h-BN flakes as a colloidal dopant in a nematic LC.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…For example, the epitaxial interactions between the nematic LC and the hexagonal lattice of graphene, molybdenum diselenide, and tungsten diselenide deposited [1][2][3][4][5][6][7][8][9][10] demonstrate that the LC can achieve a planar-aligned state on these 2D hexagonal nanostructures. Our group has recently shown that the 2D hexagonal boron nitride (h-BN) film can be successfully employed as a planar-alignment agent as well as an ion-capturing agent in electro-optic LC devices [11][12][13]. Here we report the effects of ultrafine 2D h-BN flakes as a colloidal dopant in a nematic LC.…”
Section: Introductionmentioning
confidence: 95%
“…We have recently shown that when an h-BN nanosheet is utilized as a planar-alignment agent in an LC the cell, the h-BN nanosheet captures a significant amount of free ion impurities from the LC by ion-trapping process [11]. It has been also shown that the reduction of free ions in the LC results in a reduced γ 1 [5,9,[27][28][29].…”
Section: Rotational Viscosity and Pretilt Anglementioning
confidence: 99%
See 1 more Smart Citation
“…The absence of such a peak in the h-BN/AZO case indicates a lower ion concentration in the medium, possibly due to the better ion trapping capability of the h-BN layer. 33,53 The relationship between N and the integral of transient/ ionic current is given by:…”
Section: Electrical and Electro-optic Studiesmentioning
confidence: 99%
“…27 Another emphatic aspect that should be borne in mind is that the traditional methods employed to have planar LC orientation utilize the interaction of the terminal chain of the LC with the aligning layer. The latest development in this area is to use layers of twodimensional (2D) materials like graphene, [28][29][30] hexagonal boron nitride (h-BN), [31][32][33][34][35][36] molybdenum diselenide (MoSe 2 ), 37 tungsten diselenide (WSe 2 ), 37,38 highly oriented pyrolytic graphite (HOPG), 39 molybdenum disulfide (MoS 2 ), 40 etc., for this purpose. The epitaxial interaction between the ubiquitous phenyl ring of the liquid crystal and the hexagon of the 2D material results in planar alignment of the LC molecules.…”
Section: Introductionmentioning
confidence: 99%